2005
DOI: 10.1158/0008-5472.can-04-2694
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Endogenous Gene Expression in Human Non–Small Cell Lung Cancer Cells by Estrogen Receptor Ligands

Abstract: Estrogen receptor (ER) agonists and antagonists elicit distinct responses in non-small cell lung cancer (NSCLC) cells. To determine how such responses are generated, the expression of ERa a, ERh h, and ER coregulators in human lung fibroblasts and human NSCLC cell lines was evaluated by immunoblot. Ligand-dependent estrogenic responses in NSCLC cells are probably generated via ERB and the p160 coactivator GRIP1/ TIF2, because expression of these proteins was detected, but not full-length ERA or the p160 coacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
122
2
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 39 publications
10
122
2
8
Order By: Relevance
“…The higher prevalence for methylation of this gene in spontaneous tumors from the B6C3F1 mouse parallels our previous findings in spontaneous lung tumors from the A/J mouse (20). This finding suggests that silencing of the ER-a gene is important for the development of tumors arising spontaneously in the mouse lung possibly through effects on cell proliferation (27,28). Few studies have examined methylation of this gene in human lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence for methylation of this gene in spontaneous tumors from the B6C3F1 mouse parallels our previous findings in spontaneous lung tumors from the A/J mouse (20). This finding suggests that silencing of the ER-a gene is important for the development of tumors arising spontaneously in the mouse lung possibly through effects on cell proliferation (27,28). Few studies have examined methylation of this gene in human lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of studies with conflicting data regarding ERa and ERb expression in human lung cancer and in lung cancer cell lines (Croxtall et al 1994, Caltagirone et al 1997, Omoto et al 2001, Radzikowska et al 2002, Stabile et al 2002, 2005, Hershberger et al 2005 and only two studies directly comparing ER expression in lung cancer specimens and cell lines in males and females (Fasco et al 2002, Mollerup et al 2002. One study reported similar levels of ERa and ERb in females and males (Mollerup et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The ER-α gene has been associated with elevated lung cancer risk (12,20,21,(26)(27)(28). However, the association between polymorphisms of XbaI and PvuII in the ER-α gene and the risk of developing lung cancer remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ERs reportedly inhibit proliferation and invasion of breast and lung cancer cells (7,28). Extranuclear forms of ER play a role in promoting downstream signaling for hormone-mediated proliferation and survival of breast as well as lung cancers and offer a new target for anti-tumor therapy (22).…”
Section: Discussionmentioning
confidence: 99%